Miejsce oceny cyklu życia w systemie zarządzania środowiskowego - Izabela Samson-Bręk; Aleksandra Filip (Studia Ecologiae et Bioethicae)
This publication was presented characteristics of the environmental life cycle assessment LCA (Life Cycle Assessment) as one of the methods included in the environmental management system (EMAS). Discusses also the various stages of analysis and guidance on the principles of its preparation regulated by the ISO 14000 standards (International Organization for Standardization), as well as paid attention to the key elements which determine the outcome of the assessments.